O dogma do cartel e a seletividade do direito concorrencial brasileiro - Souza, Ricardo Noronha Inglez de (2022)
The competition law has focused its mayor efforts and resources in the persecution of cartels. Cartels are considered the most dangerous violation in the contexto of the competition law. Some entities like the Organisation for Economic Co-operation and Development (OECD) and the International Competition Network (ICN) have indicated such priority for the policies to promote free competition. Nonetheless, there are several reasons to challenge such paradigm, mainly for the Brazilian context. Particularly. Here are three aspects that challenge the international proposition: (i) structural context of markets within the Brazilian economy, (ii) net effect over the welfare of unilateral conduct vis-à-vis cartels, and (iii) the efficacy of the use of public resources for such policy. The structure of markets in different countries and at different times could indicate different approaches. On the one hand, the collusion among competitors may indicate greater potential for harm. On the other hand, however, the net result may be the same – i.e. charging of supra-competitive prices by collude competitors and the maintenance of supra-competitive prices by the dominant undertaking. Finally, the cost of antitrust law enforcement can be another element to redefine that priority. Through this analysis, it was intended to answer if the international tendency to prioritize the persecution against cartels is adequate to the Brazilian reality (from an economic and legal perspectives)